(untitled) (Lectio: Journal of Language and Language Teaching, 2025)
This research aims to analyze the translation strategies of pragmatic expressions in English Indonesian subtitles of Netflix films, focusing on how translators convey meaning, politeness, and communicative intent across cultural and linguistic boundaries. Using a qualitative descriptive approach, the study examines two selected films, The Intern (2015) and Don’t Look Up (2021), through the lens of pragmatic analysis and translation strategy theory proposed by Molina and Albir (2020) and Díaz Cintas and Remael (2021). Data were collected from 300 utterances containing pragmatic functions such as directives, expressives, commissives, and representatives. The results reveal that the most frequently used strategies are equivalence (38%) and adaptation (25%), followed by modulation, omission, and explicitation. These strategies effectively maintain the communicative intent of the source text while adjusting to Indonesian cultural norms and subtitle constraints. Overall, the study concludes that successful audiovisual translation requires balancing linguistic accuracy with pragmatic and cultural appropriateness to ensure audience comprehension and engagement